Maximizing Markerless Motion Capture Data Processing Speed: Enabling Efficient Reporting: 222...American College of Sports Medicine (ACSM) Annual Meeting, May 27-30, 2025, Atlanta, Georgia. - Edwards, Nathan A.; Caccese, Jaclyn B.; Hagen, Joshua A.; Onate, James A. (Medicine & Science in Sports & Exercise)
The article focuses on the development and application of markerless motion capture technologies in research, specifically examining how data collection and processing methods affect analysis time. The study involved four participants performing various movements, with data collected and analyzed under different conditions, including trial length, sample rate, and GPU configurations. Results indicated that longer trial lengths and higher sample rates significantly increased analysis time, while improved GPU quality reduced it. The findings suggest that optimizing these variables can enhance real-time data quality control and feedback for participants, with the fastest configuration allowing for a 10-second walking trial to be analyzed in 65 seconds. The research was partially funded by the NSF Industry/University Cooperative Research Program.